Copepods associated with scleractinian corals: a worldwide checklist and a case study of their impact on the reef-building coral Pocillopora damicornis (Linnaeus, 1758) (Pocilloporidae) - Cheng, Yurong; Mayfield, Anderson B.; Meng, Peijie; Dai, Changfeng; Huys, Rony (Zootaxa, 2016)
The Cnidaria have more symbiotic copepods than any other group of invertebrates, and the greatest numbers of these associates occur on hard corals. A review of the scattered literature on the diversity and taxonomic composition of scleractinian-associated copepods and their hosts revealed a total of 148 coral species, representing 66 genera and 15 families that serve as hosts to copepods. At present, 363 copepod species, representing 99 genera, 19 families and three orders, have been recorded as associates of scleractinian corals. The total included 288 cyclopoids, 68 siphonostomatoids and seven harpacticoids. Within the Cyclopoida the representation of species varied greatly among the 13 families, with a disproportionate number of species belonging to the Anchimolgidae (141 species) and Xarifiidae (92 species). Data on host utilization and geographical distribution of all copepods living symbiotically with hard corals is synthesized and host specificity patterns are highlighted. The prevalence, intensity, density, and biodiversity of copepod infection of 480 colonies of the reef-building coral Pocillopora damicornis (Linnaeus, 1758) from Nanwan Bay, southern Taiwan were documented between July 2007 and November 2008. It was hypothesized that certain environmental factors and physiological coral traits, such as the density of Symbiodinium, could influence these infection parameters. Analysis revealed that ectoparasitic copepods were the most likely to infect P. damicornis, and that Asteropontius minutus Kim, 2003 accounted for more than 50% of total copepod density in July–September 2007 when temperatures were high and bleaching occurred in 75% of the sampled colonies. The data further showed that copepod virulence may be related to their life history strategies, as well as to Symbiodinium density, surface area of the host coral colonies, and concentration of nitrate and chlorophyll-a in the surrounding seawater. By tracking the abundance, diversity, and performance of infectious copepods prior, throughout, and after a natural bleaching event, the potential to use these parasites as bioindicators for predicting the future physiological performance of P. damicornis in response to environmental change, particularly bleaching events, may ultimately be further explored, developed and maximized. Humesimyzon Kim, 2010, previously placed in the Asterocheridae, is tentatively transferred to the recently resurrected family Coralliomyzontidae. The authorship and spelling of Pseudanthessius thorellii (Brady, 1880) are corrected.